2015
DOI: 10.1073/pnas.1510527112
|View full text |Cite
|
Sign up to set email alerts
|

Neural systems supporting linguistic structure, linguistic experience, and symbolic communication in sign language and gesture

Abstract: Sign languages used by deaf communities around the world possess the same structural and organizational properties as spoken languages: In particular, they are richly expressive and also tightly grammatically constrained. They therefore offer the opportunity to investigate the extent to which the neural organization for language is modality independent, as well as to identify ways in which modality influences this organization. The fact that sign languages share the visual-manual modality with a nonlinguistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
6
43
0
Order By: Relevance
“…Research in the last several decades has revealed that sign languages possess the same core properties of language as spoken ones (Stokoe, 1960;Bellugi & Klima, 1976;Klima & Bellugi, 1979;Petitto 1994;Sandler & Lillo-Martin, 2006), as well as similar overall neurobiological organization (Hickok et al, 1996;Neville et al, 1998;Petitto et al, 2000;Macsweeney et al, 2002;Emmorey et al, 2007;Mayberry et al, 2011). In particular, sign languages appear to rely on the same underlying lexical-syntactic and semantic systems as for spoken languages (MacSweeney et al, 2006;Leonard et al, 2012;Newman et al, 2015;Matchin et al, 2017b).…”
Section: Sign Languagementioning
confidence: 99%
“…Research in the last several decades has revealed that sign languages possess the same core properties of language as spoken ones (Stokoe, 1960;Bellugi & Klima, 1976;Klima & Bellugi, 1979;Petitto 1994;Sandler & Lillo-Martin, 2006), as well as similar overall neurobiological organization (Hickok et al, 1996;Neville et al, 1998;Petitto et al, 2000;Macsweeney et al, 2002;Emmorey et al, 2007;Mayberry et al, 2011). In particular, sign languages appear to rely on the same underlying lexical-syntactic and semantic systems as for spoken languages (MacSweeney et al, 2006;Leonard et al, 2012;Newman et al, 2015;Matchin et al, 2017b).…”
Section: Sign Languagementioning
confidence: 99%
“…A similar network of left-lateralized frontotemporal areas is involved in processing English, Mandarin Chinese, and various sign languages (e.g., Newman, Supalla, Fernandez, Newport, & Bavelier, 2014;Chee et al, 1999;Neville et al, 1997). Moreover, the seeds of typical language processing appear to be present early on in the developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging studies also indicate that when deaf adults process lexical manual gestures, the activity in language related brain regions is greater than it is for hearing individuals (Cardin, Orfanidou, Rönnberg, Capek, Rudner, & Woll, 2013;Li, Xia, Zhao, & Qi, 2014;Newman, Supalla, Fernandez, Newport, & Bavelier, 2015). These findings demonstrate that the processing of manual gestures changes with sign language experience.…”
Section: Efficient Language Processing and Imitationmentioning
confidence: 82%
“…Although an associative account of imitation suggests that motor expertise, like being a sign language user, should provide an advantage regarding imitation of manual gestures, the theory also suggests that representations that are close enough to a target behavior might be sufficient (Heyes, 2016). On the other hand, sign language experience does seem to lead to changes in the neural processing of any type of manual gestures in adults (Newman et al, 2015;but see, e.g., Cardin et al, 2016). This suggests that with development, a difference between signing and non-signing individuals might emerge.…”
Section: Gesture Type and A Surprising Effect Of Sign Language Experimentioning
confidence: 99%